The systemic inflammation response index as a significant predictor of short-term adverse outcomes in acute decompensated heart failure patients: a cohort study from Southern China - Xie, Lin; Wang, Qun; Lu, Hengcheng; Kuang, Maobin; He, Shiming; Xie, Guobo; Sheng, Guotai; Zhang, Shuhua; Wang, Wei; Zou, Yang (Frontiers in Endocrinology, 2024)
ObjectiveThe deterioration of acute decompensated heart failure (ADHF) is associated with abnormal activation of inflammatory pathways. This study aims to evaluate the impact and predictive value of a novel inflammatory marker, the systemic inflammation response index (SIRI), on short-term adverse outcomes in ADHF patients.MethodsThis retrospective cohort study included 1,448 ADHF patients from Jiangxi Provincial People’s Hospital between 2019-2022. SIRI was calculated using the formula: (neutrophil count × monocyte count)/lymphocyte count. In the correlation analysis, the study outcome was the 30-day mortality in patients with ADHF. Cox regression analysis and receiver operating characteristic curves were employed to investigate the risk assessment and predictive value of the SIRI for 30-day mortality in ADHF patients. Finally, we also exploratively assessed the mediation effect of nutritional factors (albumin: Alb, total cholesterol: TC, and lymphocyte count) on the association between SIRI and 30-day mortality in ADHF patients.ResultsDuring the 30-day follow-up, 53 deaths were recorded. Mortality rates across SIRI tertiles were 0.62%, 2.07%, and 8.28%, respectively. There was a significant linear positive correlation between SIRI and 30-day mortality in ADHF patients (HR: 1.21; P for non-linearity = 0.113). Additionally, compared to ADHF patients with low SIRI, those with high SIRI had a 685% increased risk of 30-day mortality (HR: 7.85). Furthermore, receiver operating characteristic curve analysis demonstrated that SIRI significantly improved the predictive value for 30-day mortality in ADHF patients compared to neutrophil count, monocyte count, and lymphocyte count alone (AUC: neutrophil count 0.7633, monocyte count 0.6835, lymphocyte count 0.7356, SIRI 0.8237; all DeLong P<0.05). Mediation analyses indicated that, except for lymphocyte count, both Alb and TC had significant indirect effects on the SIRI-related 30-day mortality in ADHF patients; Specifically, Alb accounted for approximately 24.46% of the mediation effect, while TC accounted for approximately 13.35%.ConclusionThis cohort study based on a Southern Chinese population demonstrates a significant linear positive correlation between SIRI and 30-day mortality in ADHF patients, highlighting its substantial predictive value. Incorporating SIRI into the monitoring regimen of ADHF patients may be crucial for preventing further disease progression.